Polycentric irrigation water governance: irrigation water users associations service delivery in Ketar Subbasin, Ethiopia - Sida, Y. G.; Simane, B.; Assefa, E.; Haileslassie, Amare (Academic Journals, 2022)
Polycentric irrigation water governance allows community institutions to deliver better irrigation services. This study examined the Irrigation Water User Associations (IWUAs) service delivery performance in the Ketar subbasin, Ethiopia, focusing on four irrigation schemes. The irrigation water user associations in the subbasin were measured on their legal registration and financial status, while the four schemes were examined on their bylaw implementation, decision transparency, water allocation, and infrastructure management. Three hundred eleven (311) randomly selected irrigators were surveyed. The study showed that 73 and 21% of the modern and traditional IWUAs in the subbasin are legally registered and collect an average ETB 1200/year/ha which is insignificant for O&M. The four schemes' water distribution disparity ranges from 3.5 to 8.4 L/s at farmers' plots. 47 and 62% of the respondents depicted their dissatisfaction with the water allocation and satisfaction with IWUAs' decision-making transparency, respectively. The study also revealed that the IWUAs are compounded with weak infrastructure management that resulted in substantial water loss ranging from 12 to 49%. Besides, 70% of respondents witnessed a lack of gender-based irrigation incentives for female irrigators. Improving these services makes the polycentric irrigation water governance play an exponential beneficial role in alleviating the consequence of unregulated water use.